Evaluation of Cigarette Tax Revenue in Northern Province (Case Study at the Regional Revenue Agency of North Sulawesi Province) - Graciella Puasa; Inggriani Elim; Syermi Mintalangi (PT FORMOSA CENDEKIA GLOBAL, 2023)
Tax revenue is important for a region, moreover tax revenue is used to support development in the region. Cigarette tax is a levy on cigarette excise collected by the central government. The aim of this research is to evaluate cigarette tax revenue at the Regional Revenue Agency of North Sulawesi Province. The research method used is descriptive qualitative. Data collection methods are interviews and documentation. The results of the research show that the implementation of cigarette tax revenues by BAPENDA of North Sulawesi Province is in accordance with North Sulawesi Governor Regulation number 4 of 2017 concerning Guidelines for Implementing Provincial Tax Profit Sharing and Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments.